SENAM HAMIL METODE AIR UNTUK MENGURANGI NYERI PUNGGUNG KEHAMILAN: LITERATURE REVIEW - Siti Noor Hasanah; Friscila, Ika (LPPM Universitas Sari Mulia, 2023)
Background: Approximately 50% of pregnant women experience back pain and 10% of pregnant women with chronic back pain. Back pain in pregnancy is often experienced when entering the 6th month of pregnancy. About 80% of women will experience back pain at some point during pregnancy due to changes in the musculature of the spine (70%). Water method pregnant exercise is a form of exercise with a lower dangerous risk compared to weight-bearing exercise without the water method. This exercise provides a feeling of lightness and also ease when moving, better thermoregulation because they are immersed in water, hydrostatic pressure which is also able to reduce edema that can occur during pregnancy, is also able to prevent and treat low back pain. Objective: To find out the effectiveness of water method pregnancy exercise for pregnant women to reduce discomfort during pregnancy, especially back pain. Methods: This study used an electronic bibliographic database with database searches using PubMed and Sciencedirect conducted systematically from 2018 to 2022. Quality articles were selected based on inclusion criteria and extraction results from 283 articles into 5 reviewed articles. Results: The results of the review show that there is an effect of pregnancy exercise using the water method to reduce pain intensity and discomfort during pregnancy and reduce injuries during exercise compared to pregnancy exercise without using the water method. Conclusion: Doing exercise using the water method can reduce back pain, low back pain and reduce discomfort in pregnancy (musculoskeletal problems) so that pregnancy goes well and healthy and even reduces pain during labor. Keywords: Pregnancy, Water Exercise, Low Back Pain